Analisis Perjanjian Kerjasama Penyelenggaraan Seminar Secara Daring - Rohman, Afif; Mediawati, Noor Fatimah (ResearchJet Journal of Analysis and Inventions, 2024)
This research raises the issue of the cooperation agreement between PT. Kreen Entertainment Indonesia with CV. Generation of Superior AR. The agreement only consists of 5 articles. The purpose of this study was to analyze the cooperation agreement between PT Kreen Entertainment Indonesia and CV. Generation of Superior AR. So, this research needs to be analyzed with the elements of the agreement between PT. Kreen Entertainment with CV. Generation of Superior AR. The research method used is the normative legal method. The results of this study indicate that the placement of the MoU in the title is not appropriate. This is because the MoU is a preliminary agreement. While this agreement consists of several articles, one of which regulates the rights and obligations of the parties. However, judging from the elements of the agreement, the accidental element has not been seen in the agreement. The benefits of this research are additional knowledge related to the analysis of the elements of the Cooperation agreement between PT. Kreen Entertainment Indonesia with CV. Superior Generation AR.